Homogeneización de las series de temperatura del aire en la República Checa durante el período instrumental - Stepánek, Petr (Geographicalia, 2016)
This paper deals with homogenization of monthly, seasonal and annual air temperature series of almost 200 stations of the Czech Republic measuring during a period of instrumental measurements (since 1771). For homogeneity testing there were used three relative homogeneity tests: Standard Normal Homogeneity Test by Alexandersson (19861, Bivariate Test of Maronna and Yohai(1978) and technique of Vincent (1996). Reference series were created by several ways to increase a number of results and thus to make the results more confident. All analysis in this paper are based on the author's software AnCliin and ProcData (software Sor automatic processing of climatological data, homogenizing, adjusting, analyzing etc.). AnClitn software is available at http://www.sci.muni.cz/-pest.
Keywords: Temperature. Homogeneization. AnClim software. ProcData software. Czech Republic.